Rethinking Japanese Feminisms - Bullock, Julia C.; Kano, Ayako; Welker, James (University of Hawai'i Press, 2017)
''Rethinking Japanese Feminisms'' offers a broad overview of the great diversity of feminist thought and practice in Japan from the early twentieth century to the present. Drawing on methodologies and approaches from anthropology, cultural studies, gender and sexuality studies, history, literature, media studies, and sociology, each chapter presents the results of research based on some combination of original archival research, careful textual analysis, ethnographic interviews, and participant observation. Building on more than four decades of scholarship on feminisms in Japanese and English, as well as decades more on women's history, this book offers a diverse and multivocal approach to scholarship on Japanese feminisms unmatched by existing publications. It will be at home in the hands of students and scholars, as well as activists and others interested in gender, sexuality, and feminist theory and activism in Japan and in Asia more broadly.